Technology-enhanced learning and teaching in anaesthesia: is it the time to move forward? - Ramly, Nur Fariza; Alias, Nurfatihah; Saw, Yee Horng; Mohamad Saad, Noor Liyana (Malaysian Society of Anaesthesiologists, 2021)
In the midst of the COVID-19 pandemic, medical education in hospitals and universities is severely affected. On the verge of sudden conversion to online education, there are many different aspects of it that triggers discomfort to the educators and the students. However, there are also many areas that have proven to be beneficial for medical education. Adapting the online technology into medical education should be blended with the conventional model of teaching and learning, not to replace or move away from it. A more precise online model of teaching and learning should be developed by including the concept of adult learning and implementing the model based on knowledge acquisitions, clinical skills development, communication skills and professionalism. A flexible model that is learner-centric, incorporates active participation and networking, with microlearning modules, is an ideal model for medical education, including anaesthesia education.